Characterization of OXA-25, OXA-26, and OXA-27, Molecular Class D β-Lactamases Associated with Carbapenem Resistance in Clinical Isolates of Acinetobacter baumannii - Afzal-Shah, Mariya (American Society for Microbiology, 2001)
Carbapenem resistance in Acinetobacter spp. is increasingly being associated with OXA-type β-lactamases with weak hydrolytic activity against imipenem and meropenem. Such enzymes were characterized from Acinetobacter isolates collected in Belgium, Kuwait, Singapore, and Spain. The isolates from Spain and Belgium had novel class D β-lactamases that were active against carbapenems. These were designated OXA-25 and OXA-26, respectively, and had >98% amino acid homology with each other and with the OXA-24 enzyme recently described by others from an Acinetobacter isolate collected elsewhere in Spain. The isolate from Singapore had OXA-27 β-lactamase, another novel class D type with only 60% homology to OXA-24, -25, and -26, but with 99% homology to OXA-23 (ARI-1), described previously from an Acinetobacter baumannii isolate collected in Scotland. Sequence data were not obtained for the carbapenem-hydrolyzing OXA enzyme from the isolate from Kuwait; nevertheless, the enzyme was phenotypically similar to OXA-25 and -26. The enzymes OXA-23, -24, -25, -26, and -27 retained the STFK and SXV motifs typical of class D β-lactamases, but the YGN motif was altered to FGN. The KTG motif was retained by OXA-27 and -23 but was replaced by KSG in OXA-24, -25, and -26. OXA-25 and -26 enzymes were strongly active against oxacillin, but unusually for an OXA-type β-lactamase, OXA-27 had apparently weak activity, although measurement was complicated by biphasic kinetics. None of the new enzymes was transmissible to Escherichia coli recipients. Many Acinetobacter isolates are multiresistant to other antibiotics, and the emergence of class D enzymes with carbapenem-hydrolyzing activity is a disturbing development for antimicrobial chemotherapy.